PENDEKATAN TASK CENTERED SYSTEM DESIGN PADA SISTEM INFORMASI PENYEWAAN GEDUNG SERBAGUNA - Tiara Sabni Hidayah; Hengky Anra; Helen Sastypratiwi (PT. Saha Kreasi Indonesia, 2025)
Multipurpose venue rentals in Pontianak are still largely handled manually, leading to inaccuracies in schedules, room availability, and transactions. This study designs and evaluates a web-based rental information system UI/UX using the Task-Centered System Design (TCSD) approach. The four TCSD stages identification, user-centered requirement analysis, design as scenario, and walkthrough evaluate were applied to map key user tasks (T1–T6), build user flows, and produce a high-fidelity Prototype. Usability was assessed with Maze remote testing and the System Usability Scale (SUS) on 15 participants. Results show a Maze usability score of 96 (High) and an average SUS score of 81.3 (Excellent), indicating that the Prototype is easy to learn, consistent, and effective. A relatively higher mis-click rate (21.1%) on package-selection highlights opportunities to refine selection controls and calendar affordances.